The Role of Extrinsic and Intrinsic Motivation to Maintain Employee Performance Productivity During Work From Home (WFH): A Case Study of a Private University in Jakarta - Supriyono, Supriyono; Susmonowati, Trinik (Technium Social Sciences Journal, 2022)
This research is intended to answer the question of how employees perform during Work From Home, what obstacles are encountered by employees and leaders during Work From Home, and how employees can be motivated to continue to maintain productivity during Work From Home. This is a qualitative research using a case study approach. Data collection was obtained from the results of semi-structured interviews with 10 informants consists of 8 staff from 4 departments and 2 managers. The results of this study prove that in order to be able to maintain their performance during a pandemic, extrinsic motivation from every supervisor is needed to motivate their staff. This research also proves that superiors who never motivate their staff and only demand that employees have intrinsic motivation from within themselves will not be able to maintain the productivity of employee performance.